New apinnate Prionospio (Annelida: Spionidae) species from southeastern Brazil - Peixoto, Antônio João Malafaia; Paiva, Paulo Cesar (Zootaxa, 2020)
Eleven apinnate Prionospio Malmgren, 1867 species were recorded from southeastern Brazil, both from coastal environments and the continental slope. Ten of these species—Prionospio acuta sp. nov., P. fosterae sp. nov., P. kinbergi sp. nov., P. hartmanae sp. nov., P. mutata sp. nov., P. cinthyae sp. nov., P. corrugata sp. nov., P. alexandrae sp. nov., P. biancoi sp. nov., and P. quadrilamellata sp. nov. are new to science, whereas P. cf. delta Hartman, 1965 has been previously recorded in Brazil. Most novel species correspond to multibranchiate forms, but can be distinguished based on the prostomial shape, presence of dorsal crests, branchial morphology, presence of sabre chaetae, morphology of parapodial lamellae, and hook morphology. An identification key and a comparison table to all eleven species recorded in the area are provided.